Pharmacophore mapping studies on indolizine derivatives as 15-LOX inhibitors - Vikas Sharma; Vipin Kumar (Faculty of Pharmacy, Cairo University, 2015)
This investigation analyzes the common chemical features for 15-lipoxygenase (15-LOX) inhibitors to develop ligand-based pharmacophore models for lipoxygenase inhibitory activity. The present model is based on a dataset of 47 indolizine derivatives that exhibit inhibition against 15-LOX enzyme isolated from soybeans. Pharmacophore models were developed with pharmacophoric features namely: aromatic ring (R) and hydrogen bond acceptor (A). The pharmacophore hypothesis ARRR.5 with R2 value 0.9451 yields a 3D-QSAR model which is statistically significant and the best pharmacophore hypothesis. External validation is performed to evaluate the robustness of the model and in this study; it was performed on a test set where correlation coefficient between experimental and predicted activity values was found to be 0.8508. The study suggested that pharmacophore modeling approach could be used as a tool for the development of lead structures.